Pengaruh Harga Dan Kualitas Produk Terhadap Keputusan Pembelian Produk Wardah Glasting Liquid Lip Konsumen Guardian Mall Bassura - Nadia Putri Yulanda; Arief Rachmawan Assegaf (Jurnal Manajemen Bisnis Krisnadwipayana, 2026)
The purpose of this study is to analyze the influence of price and product quality on the purchasing decision of Wardah Glasting Liquid Lip products for consumers at Guardian Mall Bassura. This study uses a quantitative method with a survey approach. The sample was selected using purposive sampling with the criteria of female respondents who purchased Wardah products. The number of samples was calculated based on the lemeshiw calculation of 100 respondents. Data analysis used multiple and simple linear regression. The results of the study partially show that price has an effect on purchasing decisions and product quality has an effect on purchasing decisions. Simultaneously, price and product quality have an effect on purchasing decisions for Wardah Glasting Liquid Lip products for consumers at Guardian Mall Bassura.